2019
DOI: 10.1016/j.jvs.2018.03.424
|View full text |Cite
|
Sign up to set email alerts
|

Statins reduce mortality and failure to rescue after carotid artery stenting

Abstract: Statin use is associated with significant reduction in mortality and failure to rescue in patients who develop major complications (stroke/MI) after CAS. Therefore, statin use should be strongly encouraged in all patients undergoing CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
(48 reference statements)
3
13
0
Order By: Relevance
“…We insure that all our patients are on statin and aspirin as well as β-blockers and for CAS dual antiplatelet agents is mandatory. 15,16 Statins have been shown to be protective for mortality following CEA and CAS in previous studies; similarly in this study, statins have shown 71% reduction in mortality. 16,17 We patch all our CEA under EEG and evoked potential monitoring with selective shunting.…”
Section: Discussionsupporting
confidence: 80%
“…We insure that all our patients are on statin and aspirin as well as β-blockers and for CAS dual antiplatelet agents is mandatory. 15,16 Statins have been shown to be protective for mortality following CEA and CAS in previous studies; similarly in this study, statins have shown 71% reduction in mortality. 16,17 We patch all our CEA under EEG and evoked potential monitoring with selective shunting.…”
Section: Discussionsupporting
confidence: 80%
“…However, this latter evidence was only borderline significant, and the study did not consider time-dependent events that could have influenced mortality, thus misestimating the potential beneficial effect of statins on different outcomes. Similar results on post-operative mortality were shown in the recent large retrospective analysis of Rizwan et al on data of the Premier Healthcare Database, a large American database that includes data of more than 700 U.S. hospitals [ 6 ].…”
Section: Introductionsupporting
confidence: 77%
“…The protective effect of statins on the onset of peri-procedural complications and long-term cardiovascular events and mortality after angioplasty and stenting has been demonstrated in coronary and other arterial sites [ 4 , 20 ], as well as in carotid surgical endarterectomy [ 21 ]. Previous studies have extended this evidence also in carotid artery stenosis regarding peri-procedural complications [ 6 , 11 , 13 ] and 5-years mortality [ 5 ]. Our study confirms previous observations showing a beneficial effect of statins on survival rate and extends this observation over 8 years after CAS procedure also providing additional evidence of beneficial effect of these drugs on new MACE occurrence and, particularly, on the new onset of fatal and non-fatal stroke.…”
Section: Discussionmentioning
confidence: 83%
“…Studies of statin use in CEA or carotid artery stent (CAS) surgery show apparent reductions in major adverse cardiac and cerebrovascular events (MACE), including a nearly fourfold reduction in stroke and seven-fold reduction in mortality. 33,34 In a recent large study of CAS, 35 a subgroup analysis showed greatest benefit from statins in patients with no history of coronary artery or cerebrovascular disease, with 67% and 40% reduction in mortality and stroke, respectively, suggesting that statins may be more effective if intervention is undertaken earlier to prevent development of large unstable plaques.…”
Section: Perioperative Statins For Major Surgerymentioning
confidence: 99%